2002
DOI: 10.2134/agronj2002.4350
|View full text |Cite
|
Sign up to set email alerts
|

Corn Yield Response to Nitrogen Fertilizer Timing and Deficiency Level

Abstract: Nitrogen fertilizer is typically applied to corn (Zea mays L.) shortly before planting, but there are several reasons why later N applications may be of interest: to spread work away from the busy planting season, to avoid the frequent wet field conditions in spring, to reduce or remedy in‐season N loss in wet years, or to allow use of in‐season diagnostic tools. One of the obstacles to the use of later N applications is the fear that irreversible yield loss will occur due to N stress. Our objective was to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
133
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(146 citation statements)
references
References 22 publications
8
133
2
2
Order By: Relevance
“…Finally, the reduced period of early crop growth, usually observed with delayed N application when maize is sown after black oat, has less effect on grain yield when corn is planted in the beginning of spring (Russele et al, 1983;Scharf et al, 2002). At this time, air temperatures are low and maize grows slowly, which gives the crop more time to recover from early cycle stresses without compromising the formation of yield component (Sangoi, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the reduced period of early crop growth, usually observed with delayed N application when maize is sown after black oat, has less effect on grain yield when corn is planted in the beginning of spring (Russele et al, 1983;Scharf et al, 2002). At this time, air temperatures are low and maize grows slowly, which gives the crop more time to recover from early cycle stresses without compromising the formation of yield component (Sangoi, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it may decrease the disparity of yield losses due to N stress if rainy springs delay the planned side-dress application time (Scharf et al, 2002). Conversely, the anticipation of N fertilization may favor N loss by leaching due to the low N uptake capacity of maize in early growth stages (Blackmer et al, 1992;Scherer, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Correlations found for the 6 July AVIRIS image and 16 July Landsat 5 TM image were mostly caused by the data from the plots with 0 kg N ha −1 . Scharf et al (2002b) found that nitrogen fertilizer applications could be delayed during maize vegetative growth (growth stages V1-V15), but losses in yield occurred when maize reaches reproductive growth stages without sufficient nitrogen. The AVIRIS data acquired on 6 July indicated that it is possible to use remote sensing to detect severe nitrogen deficiency (0 kg N ha −1 plots).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen fertilizer rates needed for corn vary largely among fields and also within fields (Scharf et al, 2002), due to variations in crop uptake demand, soil N supply, and losses from the soil. Identifying the EONR is very important in high N-demanding crops such as corn, to maximize profitability and to reduce N losses to the environment (Wang et al, 2003;Kyveryga et al, 2009).…”
mentioning
confidence: 99%